The Reflective Functioning Questionnaire-Revised- 7 (RFQ-R-7): A new measurement model assessing hypomentalization. - Zsolt Horváth; Orsolya Demetrovics; Borbála Paksi; Zsolt Unoka; Zsolt Demetrovics (PLoS ONE, 2023)
Although it is a widely used questionnaire, limitations regarding the scoring procedure and the structural validity of the eight-item Reflective Functioning Questionnaire (RFQ-8) were raised. The present study aimed to examine further the latent dimensionality of the RFQ-8 and to examine linear and non-linear associations between mentalization difficulties and maladaptive psychological characteristics. Data from two separate representative samples of young adults (N = 3890; females: 51.68%; mean age: 27.06 years [SD = 4.76]) and adults (N = 1385; females: 53.20%; mean age: 41.77 years [SD = 13.08]) were used. In addition to the RFQ-8, standardized questionnaires measured the levels of impulsivity, sensation seeking, rumination, worry and well-being. Confirmatory factor analysis (CFA) was used to test the model fit of competing measurement models. CFA revealed that a revised, seven-item version of the RFQ (RFQ-R-7) with a unidimensional structure showed the most optimal levels of model fit in both samples. Impulsivity, sensation seeking, rumination and worry consistently presented significant, positive, linear associations with general mentalization difficulties in both samples. Significant quadratic associations were also identified, but these relationships closely followed the linear associations between the variables and increased only marginally the explained variance. The supported unidimensional measurement model and the associations between the general mentalization difficulties factor and maladaptive psychological characteristics indicated that the RFQ-R-7 captures a dimension of hypomentalization ranging between low and high levels of uncertainty. Increasing levels of hypomentalization can indicate a risk for less adaptive psychological functioning. Further revisions of the RFQ-8 might be warranted in the future to ensure adequate measurement for hypermentalization.